Effectiveness of Using RFHDS Connected PIP System for Subsea Pipeline Vibration Control - Bi, Kaiming; Hao, Hong; Chen, Wensu (World Scientific Publishing Co. Pte. Ltd., 2018)
Pipe-in-pipe (PIP) system can be considered as a structure-tuned mass damper (TMD) system by replacing the hard centralizers by the softer springs and dashpots to connect the inner and outer pipes. With properly designed connecting devices, PIP system therefore has the potential to mitigate the subsea pipeline vibrations induced by various sources, such as earthquake or vortex shedding. This study proposes using rotational friction hinge dampers with springs (RFHDSs) to connect the inner and outer pipes. The rotational friction hinge dampers (RFHDs) are used to absorb the energy induced by the external vibration sources and the springs are used to provide the stiffness to the TMD system and to restore the original locations of the inner and outer pipes. To investigate the effectiveness of this new design concept, detailed three-dimensional (3D) finite element (FE) model of the RFHD is developed in ANSYS and the hysteretic behavior of RFHD is firstly studied. The calculated hysteretic loop is then applied to the 3D PIP FE model to estimate the seismic responses. The effectiveness of the proposed system to mitigate seismic induced vibrations is examined by comparing the seismic responses of the proposed system with the conventional PIP system. The influences of various parameters, such as the preload on the bolt, the friction coefficient and the spring stiffness, on the RFHD hysteresis behavior and on the seismic responses of PIP system are investigated and some suggestions on the RFHDS design are made.